Pengaruh beban lampu terhadap tegangan, arus, dan rpm pada turbin angin cross flow 8 sudu - Syamsi, Febrian Nur; Irfa`i, Mochamad Arif; Basuki, Basuki (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2020)
Alternative energy is a source of energy found in nature that can be directly used freely. In addition, the availability of alternative energy is infinite and can be managed sustainably. This wind energy source can be used as an electricity generator by building several wind turbine units. The problem in this research is how the influence of the load on the performance of the 8 blades cross flow wind turbine, while the purpose in this study is to find out how the load on the performance of the blades of 8 blades. The type of research I use is quantitative research. For the author's method using an experimental method, the free load variable lights 0, 3, 6 and 9 watts and the dependent variables are current, voltage and RPM. The results showed that the 8 blades cross flow wind turbine had the best performance at 0 watt load which produced 0 ampere current, 13.8 watt voltage and 354.92 RPM. while the lowest performance on a 9 watt lamp load which produces a current of 0.2088 amperes, a voltage of 9.08 volts and Rpm 301.08, the current has increased, this is because the current is directly proportional to the load power, while the voltage and RPM have decreased because generator voltage and RPM are inversely proportional to the load power used.